MAPPING OF ADMINISTRATIVE BOUNDARIES OF URUTSEWU VILLAGE, AMPEL DISTRICT, BOYOLALI REGENCY USING THE CARTOMETRIC METHOD - Muharrom, Ahmad Shahrul (Elipsoida : Jurnal Geodesi dan Geomatika, 2025)
Mapping of village administrative boundaries is one of the key aspects supporting governance, public services, and regional development planning. This research goal is to map the administrative boundaries of Urutsewu Village, Ampel Subdistrict, Boyolali Regency, with high accuracy using a cartometric method in accordance with Ministry of Home Affairs Regulation Number 75 of 2014 concerning Guidelines for Determining and Confirming Village Boundaries. The cartometric method was used to integrate various data sources, including historical maps, satellite imagery, field surveys, and administrative documents, to produce an objective and accurate boundary analysis. The results is that the administrative boundary of Urutsewu Village consists of four main segments connecting boundary node points. Differences in segment lengths were found between the existing indicative village boundary and the newly delineated boundary, resulting in a change in the village’s area from approximately 245.473 ha to 290.982 ha and in its perimeter from 8,210.949 meters to 8,918.779 meters. The boundary verification process also involved community participation as a validation step to ensure conformity with field conditions. The outputs of this research include a 1:5,000 scale boundary map of Urutsewu Village in both printed and digital formats. Keywords : village boundary, cartometric method, boundary confirming, scale, community participation